The gendered "I" in ancient literature modelling gender in first-person discourse - Cordes, Lisa; Fuhrer, Therese 1959- (De Gruyter, 2022)
Considering the ubiquity of rhetorical training in antiquity, the volume starts from the premise that every first-person statement in ancient literature is in some way rhetorically modelled and aesthetically shaped. Focusing on different types of Greek and Latin literature, poetry and prose, from the Archaic Age to Late Antiquity, the contributions analyse the use and modelling of gender-specific elements in different types of first-person speech, be it that the speaker is (represented as) the author of a work, be it that they feature as characters in the work, narrating their own story or that of others. In doing so, they do not only offer new insights into the rhetorical strategies and literary techniques used to construct a gendered ‘I’ in ancient literature. They also address the form and function of first-person discourse in classical literature in general, touching on fields of research that have increasingly come into focus in recent years, such as authorship studies, studies concerning the ancient notion(s) of the literary persona, as well as a historical narratology that discusses concepts such as the narrator or the literary character in ancient literary theory and practice
Aus der Einleitung: "The volume collects papers givn at the tenth meeting of the "European network on gender studies in antiquity" (EuGeStA) at LLMU Munich on 7-9 November 2019, and additional papers that were commissioned afterwards in order to further broaden the scope of the publication."
Keywords: Griechisch; Geschlecht; Ich-Form; Latein; Literatur; Hardcover, Softcover / Geschichte/Altertum; Aufsatzsammlung; Konferenzschrift -- 2019 -- München